A volatile semiochemical released by the fungus garden of leaf-cutting ants - Sousa, K. K. A. [UNESP]; Catalani, G. C. [UNESP]; Gianeti, T. M. R. [UNESP]; Camargo, R. S.; Caldato, N. [UNESP]; Ramos, V. M.; Forti, L. C. [UNESP] (Florida Entomological Soc, 2020)
The symbiosis between fungi and leaf-cutting ants (Hymenoptera: Formicidae) has aroused the interest of researchers about the mechanism used by ants to select plants. The nutritional needs of the fungus garden, and the absence of potentially deleterious substances from plants, are criteria for selection by foraging workers. This is supported by behavioral experiments using fungicide with baits (citrus pulp) or forage plants highly accepted by leaf-cutting ants. The fungus garden is hypothesized to emit a volatile semiochemical in response to a fungicide, which informs ants that a plant is unsuitable for its growth. The objectives of our study were to identify the volatile compounds released by the fungus garden of leaf-cutting ants in response to a fungicide, as well as to determine the behavioral response of workers to healthy and unhealthy fungus gardens. The results showed no difference in the proportion of volatile compounds released by either healthy or unhealthy fungus gardens. Analysis of the responses of ants to healthy or unhealthy fungus gardens in a dual-choice experiment revealed a strong attraction to the fungus garden, regardless of its health status. We therefore conclude that no volatile semiochemicals are emitted by the fungus garden due to the action of deleterious substances.
Keywords: Formicidae; Atta; symbiotic fungus